The Effect of Solvent-to-Coffee Ratio on Caffeine Content in Ethyl Acetate Extracts of Arabica Gayo Coffee Beans - Soeswanto, Bambang; Sihombing, Rony Pasonang; Suryadi, Joko; Hariyadi, Tri; Paramitha, Tifa; Yusuf, Yusmardhany; -, Alfiana Adhitasari (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
This paper studies the optimal ratio that gives the highest caffeine amount and improves the efficiency and quality of extraction from Arabica Gayo coffee beans. No previous studies have explored the best ratio of Gayo Arabica coffee beans to ethyl acetate solvent for extracting caffeine. The paper explains the method used, which has four main steps: preparing materials, extracting and measuring caffeine, and analyzing the results. The paper presents the experimental findings and discusses how different ratios affect caffeine content in Arabica Gayo coffee beans. It uses statistics to show significant differences between the ratios and compares them using Tukey tests. The paper concludes that the best solvent-to-coffee ratio for maximizing caffeine in ethyl acetate extracts is 1:5, resulting in a concentration of 1411.1 ppm. This ratio gives the best balance between caffeine yield and solvent usage.